Spray-dried bacterial cellulose nanofibers: A new generation of pharmaceutical excipient intended for intestinal drug delivery - Meneguin, Andreia Bagliotti [UNESP] (2020)
Defibrillation of bacterial cellulose by ultra-refining was efficient to release nanofibers (BCNF) which were spray dried with the matrices formers mannitol (MN), maltodextrin or hydroxypropylmethylcellulose. The best microsystem comprised the association of BCNF and MN, so the selected microparticles were loaded with diclofenac sodium or caffeine. Depending on the proportion of BCNF, the nanofibers collapse promoted by spray drying can occur onto surface or into microparticles core, leading to different release behaviors. Samples showed pH-dependent drug release, so the microsystem developed with the lowest BCNF concentration showed important trend to gastroresistance. Caffeine was spray dried as a free drug and for this reason it was devoid of any control over release rates. The set of results showed BCNF can be considered an interesting and potential pharmaceutical excipient for lipophilic drugs. Beyond that, BCNF association with MN can lead to novel enteric drug delivery systems based on natural polymers.